Histoenzymatic studies on the tongue of adult Indian buffalo (Bubalus bubalis) - SINGH, KULWINDER; ROY, K S (The Indian Journal of Animal Sciences, 2014)
A histoenzymatic study was conducted on the tongue of 8 adult Indian buffaloes for the demonstration of phosphatases,oxidoreductase and esterascs. The lingual epithelium, taste buds, muscles and seromucous glands wcre positive for AKPase, ACPase, SDH, LDH, G-6-PD, NADH and 17-Î² HSD. AchEase was only seen in nerve terminals. fibres and motor end plates.